(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This research paper explores the complex world of youth boxing, examining the biomechanics, physiological demands, and skill development involved in mastering the techniques necessary to succeed in the sport. The analysis includes the unique challenges faced by young boxers and how scientific principles can be applied to optimize their training and performance.